The bodies keep coming : dispatches from a Black trauma surgeon on racism, violence, and how we heal - Williams, Brian H. (Surgeon) (Minneapolis : Broadleaf Books, 2023)
"Dr. Brian H. Williams has seen it all, from gunshot wounds to traumatic brain injuries. In The Bodies Keep Coming, Williams ushers us into the trauma bay, where the wounds of a national emergency amass. Black bodies will continue to be wracked by violence, racism, and healthcare inequities until we enact changes of policy and law"--
Part I. Unconscious -- Tagged and bagged -- Demons -- My comfort and my pain -- The long blue line -- A new calling -- The Gradys -- Part II. Code yellow -- "Bald, black, and suspicious" -- Traumatic arrest -- Hail Mary -- Seconds matter -- End of watch -- Part III. Shock -- A fool for a patient -- God's token -- Backlash -- Bridge -- Part IV. Awakening -- Failure by design -- Race is not a risk factor -- Anatomy of a gunshot wound -- A moment of silence.
Includes bibliographical references.
Description based on online resource; title from digital title page (viewed on August 23, 2023).
JSTOR
Keywords: Williams, Brian H. -- (Surgeon); African American surgeons -- Biography; Surgeons -- United States -- Biography; Gunshot wounds -- Surgery -- United States; Discrimination in medical care -- United States; Racism -- United States; Gunshot wounds; Surgeons; Racism; Wounds, Gunshot; Chirurgiens noirs américains -- Biographies; Chirurgiens -- États-Unis -- Biographies; Lésions et blessures par armes à feu -- Chirurgie -- États-Unis.; Discrimination dans les soins médicaux -- États-Unis.; Racisme -- États-Unis.; Lésions et blessures par armes à feu; BIOGRAPHY & AUTOBIOGRAPHY / Medical (incl. Patients); African American surgeons; Discrimination in medical care; Racism; Surgeons; United States; Biographies